Changes in Seed Yield of Sunflower (Helianthus annuus L.) in relation to the Seed Rate and Method of Sowing - Singh, Lokendra; Parajuli, Tulsi (International Journal of Environment, 2020)
Inappropriate seed rate and sowing method contribute a significant role in low productivity of sunflowers. So, a study was conducted to assess the effect of different seed rates and sowing methods on the yield of sunflower in Ghodaghodi Municipality ward no. 2, Sandepani, far-west province, Kailali, Nepal, during spring season in 2018. The three different seed rates (8 Kg/ha, 10 Kg/ha and 12 Kg/ha) combined with three different sowing methods (broadcasting, line sowing and ridge sowing). A randomized complete block design in a 3×3 factorial arrangement with three replicates per treatment was applied. The indigenous variety of sunflower was used as a test crop. The highest stem diameter was recorded with the lowest seed rate, which remained unaffected by different sowing methods. Head diameter, seeds per head and thousand-grain weight were maximum in plants receiving seed rate of 8 kg/ha. However, the highest (2.13 t/ha) and the lowest (1.76 t/ha) grain yield were achieved with the seed rates of 10 kg/ha and 12 Kg/ha, respectively. Regarding sowing methods, head diameter, seeds per head, thousand-grain weight and grain yield (2.68 t/ha) obtained in the ridge method were statistically superior over those, obtained in line and broadcasting methods. The interaction effect of seed rate and sowing method on seeds per head suggested that maximum seeds per head were obtained with 8 kg/ha seed sown in the ridge. Our study recommended 8 kg/ha seed rate and ridge sowing of sunflower performed best in grain yield.